Ferments in the Field: Introductory Reflections on the Past, Present and Future of Communication Studies. (2nd April 2018) - Fuchs, Christian; Qiu, Jack Linchuan
Abstract: Journal of Communication (JoC) published its special issue "Ferment in the Field" in 1983 (vol. 33, no. 3). Thirty-five years later there still is a great interest in discussing the origins, current state, and prospects of our field. This special issue titled Ferments in the Field: The Past, Present and Future of Communication Studies presents 20 articles, plus this introduction, with the intention to assess the field and provoke discussions about the status of communication studies. This introductory article provides an overview of the contributions and discusses major trends in communication studies that have shaped the field since the original "ferment" issue. They include: (a) communication studies on a global scale, (b) researching communication in the fast-changing digital media environment, (c) the importance of critical communication studies, (d) the new critical and materialist turn, and (e) praxis communication and ways to address power imbalance in knowledge production.